STUDI TENTANG AKTIVITAS SEKRESI REACTIVE OXYGEN INTERMEDIATES (ROIS) MAKROFAG MENCIT YANG DISTIMULASI DENGAN PROTEIN LARUT TOXOPLASMA SELAMA INFEKSI TOXOPLASMA GONDII - Muthmainah, Muthmainah (Jurnal Kedokteran YARSI, 2005)
Toxoplasmosis is a parasitic disease caused by Toxoplasma gondii. This disease is asymptomatic, but it can elicite a problem in the immunocompromised patient and in the pregnant woman. This work was carried out to study the Reactive Oxygen Intermediates (ROIs) secretion activity of macrophages in mice stimulated with soluble protein of Toxoplasma during Toxoplasma gondii infection. In this study, 24 female Balb/c mice were used and devided into three groups. The first group was stimulated with 10 µg of soluble protein. The second group was stimulated with 10 µg of soluble protein with the addition of incomplete Freund?s adjuvant and the third group represented as control. The addition of incomplete Freund?s adjuvant to soluble protein was aimed to increase the immunogenicity of soluble protein. The stimulant was administered twice intraperitoneally with intervals of 2 weeks. Two days after the second stimulation, the mice were infected intraperitoneally with 4x102 tachyzoites of Toxoplasma gondii RH strain. On day 0, 3, 5 and 7 post infection, 2 mice from each group were sacrificed, the peritoneal macrophages were isolated and cultured to measure the ROIs secretion activity of macrophages in vitro. The Posttest Only Control Group Design was used as the experimental design. The data were analysed with One Way Anova. The result of this experiment showed that during Toxoplasma gondii infection, the ROIs secretion activity of macrophages in all groups of mice increased on day 5, and henceforth declined. The activity of macrophages from the first group and the second group were higher than that of the control group (the third group). The increment of ROIs secretion activity of macrophages in the second group was higher than that in the first group. It can be concluded that stimulation with soluble protein can increase the ROIs secretion activity of macrophages. The addition of incomplete Freund?s adjuvant to soluble protein increased the immunogenicity of soluble protein.